Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

let $a,b,c$ are real numbers,and such $a+b+c=3$,show that $$\dfrac{1}{2a^2-6a+9}+\dfrac{1}{2b^2-6b+9}+\dfrac{1}{2c^2-6c+9}\le\dfrac{3} {5}\cdots (1)$$ I find sometimes,and I find this same problem:

let $a,b,c$ are real numbers,and such $a+b+c=3$,show that $$ \frac{1}{5a^2-4a+11}+\frac{1}{5b^2-4b+11}+\frac{1}{5c^2-4c+11}\leq\frac{1}{4} $$ and this problem have some methods,you can see:

and I like this can_hang2007 methods and Honey_S methods,But for $(1)$ I can't prove it.Thank you

share|cite|improve this question
Are you allowed to use calculus? You can simply substitute a = 3 - b - c for all instances of a and then use calculus to proceed, however in the interest of time and solvability (i'm assuming have no calculators) that may not be practical. – frogeyedpeas Sep 30 '13 at 3:35
I don't like calculus,because it must be very very ugly!! I like use AM-GM,cauchy-schwarz,jenson,and so on these nice methods solve inequality! – china math Sep 30 '13 at 3:39
Are $a, b, c$ non-negative? – Macavity Sep 30 '13 at 4:04
I think this equality is true for real numbers? – china math Sep 30 '13 at 4:11
up vote 3 down vote accepted

Let $f(x) = \dfrac{1}{x^2+(3-x)^2}$. WLOG let $a \le b \le c$.

We note: $f(x) = f(3-x)$ and
if $x < 0$, then $f(x) < f(-x)$ as is obvious from signs or from $f(x)-f(-x) = \dfrac{12x}{4x^4+81}$. Using these, if $a < 0$, we also note $$f(a)+f(b)+f(c) < f(-a) + f(3-b)+f(3-c)$$ where the new arguments also fulfil the constraint.

Thus if $a < 0$, to prove the inequality holds for $(a, b, c)$, it is sufficient to show it holds for $(-a, 3-b, 3-c)$. If this also has negative variables, then one more application turns $(-a, 3-b, 3-c) \to (3+a, b, c-3)$, where the lower most value has increased by $3$ and the largest has decreased by $3$.

Using successive application of this as necessary, it is sufficient to consider cases where $a \ge 0$, i.e. where all the variables are non-negative. Now we look at the following version of the inequality,

$$-\sum_{cyc} \left(\frac{5}{2a^2-6a+9} - 1 \right) = \sum_{cyc} \frac{2(a-1)(a-2)}{2a^2-6a+9}$$

$$\frac{2(a-1)(a-2)}{2a^2-6a+9} = -\frac{2(a-1)}{5} + \frac{2(a-1)^2(2a+1)}{5(2a^2-6a+9)} \ge -\frac{2(a-1)}{5}$$

$$\implies -\sum_{cyc} \left(\frac{5}{2a^2-6a+9} - 1 \right) \ge \sum_{cyc}-\frac{2(a-1)}{5}=0 $$

Hence proved.

share|cite|improve this answer
Is the assertion "if $x < 0$, then $f(-x) < f(x)$" always true? – Joseph Quinsey Oct 23 '13 at 2:15
@JosephQuinsey It is the other way round i.e. if $x < 0, f(x) < f(-x)$, which is used in the proof, I shall edit it in. Thanks. – Macavity Oct 23 '13 at 3:36
Is a minus sign missing? $\sum_{cyc}\left(\frac{5}{2a^2-6a+9}-1\right)=\sum_{cyc}-\frac{2(a-1)(a-2)}{2a^2‌​-6a+9}$. – Joseph Quinsey Oct 23 '13 at 5:06
$\frac{2(a-1)(a-2)}{2a^2-6a+9} = -\frac{2(a-1)}{5} + \frac{(a-1)^2(2a+1)}{5(2a^2-6a+9)}$ seems to be wrong. – Joseph Quinsey Oct 23 '13 at 7:54
@JosephQuinsey Check, the missing $2$ is edited. – Macavity Oct 23 '13 at 8:30

Let $f(x) = \dfrac{1}{2x^2-6x+9}$. First let us first quickly sketch some properties of $f$ that we'll need. $f(x)=\dfrac{1}{2(x-\frac32)^2+\frac92}$, so its maximum is $f(\frac32)=\frac29$. $f~'(x)=\dfrac{6-4x}{(2x^2-6x+9)^2}$, and $f~''(x)=12\dfrac{2x^2-6x+3}{(2x^2-6x+9)^3}$. Setting $f~''(x)=0$ gives the inflection points $x=\frac32\pm\frac{\sqrt3}2$. $f$ is increasing before $\frac32$, decreasing after $\frac32$, and is concave between the inflection points. Note $f(\frac32\pm\frac{\sqrt3}2)=\frac16$.

If $a$, $b$, and $c$ are all between the inflection points, then by Jensen's inequality $$f(a)+f(b)+f(c) \le 3f(\dfrac{a+b+c}3) = 3f(1) = \frac35$$ as required.

If at least two of $a$, $b$, or $c$ are outside the inflection points, then $$f(a)+f(b)+f(c) \le \frac16+\frac16+\frac29=\frac59\lt\frac35$$

If one of $a$, $b$, or $c$ is $\gt\frac32+\frac{\sqrt3}2$, then at least one of $a$, $b$, or $c$ is $\lt\frac32-\frac{\sqrt3}2$, otherwise $$3=a+b+c\ge 2(\frac32-\frac{\sqrt3}2)+(\frac32+\frac{\sqrt3}2)=\frac92-\frac{\sqrt3}2 \approx 3.7,$$ a contradiction. And so by the previous paragraph, the required result holds.

So the only remaining case is when exactly one of $a$, $b$, or $c$ is $\lt\frac32-\frac{\sqrt3}2$, and the other two are between the inflection points. We need two estimates. First consider the case when the minimum is $\le\frac12$. (Here $\frac12$ is arbitrary, although we need to choose something very close to $\frac12$ for the following argument to work.) Then $$f(a)+f(b)+f(c) \le f(\frac12) + \frac29 + \frac29 = \frac{2}{13} + \frac49 = \frac{70}{117} \lt \frac35$$

Finally, suppose $a$ is between $\frac12$ and $\frac32-\frac{\sqrt3}2$, and $b$ and $c$ are between the inflection points. By Jensen's inequality, we need only consider the case when $b=c$, by replacing them with their mean. Then $b=(3-a)/2$. So $a\gt\frac12$ implies $b\lt\frac54$, and $$f(a)+f(b)+f(b) \lt f(\frac32-\frac{\sqrt3}2) + 2f(\frac54) = \frac16 + \frac{16}{37} = \frac{133}{222} \lt \frac35$$

share|cite|improve this answer

Here's what I've got so far. It's not a complete solution, but the ideas might be useful to someone else.

$2x^2-6x+9 =x^2+(x-3)^2 $.

If $f(x) =2x^2-6x+9 $, $f'(x) =4x-6 $ is zero at $x = 3/2$. Since $f(3/2) =9/2 $, $f(x) \ge 9/2$ for all $x$.

This means that $\dfrac1{f(x)} \le \dfrac{2}{9} $ for all $x$, so $\dfrac1{f(a)}+\dfrac1{f(b)}+\dfrac1{f(c)} \le \dfrac{6}{9} = \dfrac23 $ without any hypothesis on $a, b, c$.

If $c = 3-a-b$, $f(c) =(3-a-b)^2+(a+b)^2 $.

If $a=b=3/2$, $c = 0$ so $f(c) = 9$ so $\dfrac1{f(a)}+\dfrac1{f(b)}+\dfrac1{f(c)} = \dfrac{5}{9} < \dfrac{3}{5} $.

If $a=b=c$, $a=b=c=1$. Since $f(1) =1+4=5 $, $\dfrac1{f(a)}+\dfrac1{f(b)}+\dfrac1{f(c)} = \dfrac{3}{5} $, so this is the equality case.

If we can show that $\dfrac1{f(a)}+\dfrac1{f(b)}+\dfrac1{f(3-a-b)} $ is a maximum when $a=b=1$, that would do it.

But I don't know how right now, so I'll leave it at this.

share|cite|improve this answer

A comment to complete the other proof.

We try to show that it is enough to consider the inequality for only positive $a,b,c$. Assume $a\leq b\leq c$.

$$ \sum_{cyc}\dfrac{1}{2a^2-6a+9}= \sum_{cyc}\dfrac{1}{(b+c)^2+a^2}= \sum_{cyc}\dfrac{1}{9-2ab-2ac} $$ Now it can be seen that if $a\leq 0$ and $b\leq 0$, one can choose $(-a,-b,c)$ instead and decrease the denominator and hence increase the whole sum (similar for the case where $a<0$).

In other words, for each triple $(a,b,c)$ for which at least one of $a,b,c$ is negative, one can find another triple with whole positive elements such that the sum is increased.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.